Comparison of placenta accreta spectrum disorders diagnosed in intrapartum and antepartum period— A three year experience in a tertiary referral unit of India. (May 2019) - Mittal, Pratima; Suri, Jyotsna; Pruthi, Neha; Pandey, Divya; Bharti, Rekha
Abstract: Objective: To determine the frequency of placenta accreta spectrum (PAS) disorders and to study the demographic profile, risk factors and maternal and fetal outcomes in women with antepartum diagnosis of PAS as compared to women with diagnosis made in the intrapartum period. Study design: Retrospective analysis over a 3-year period of all patients who delivered with PAS. The cases were divided into 2 groups. Group 1 consisted of the patients who were diagnosed during the intra partum period and Group 2 was those diagnosed as PAS by ultrasound in the antepartum period. Maternal and fetal outcomes were compared between the 2 groups. The cases that underwent conservative management were also analyzed for need of secondary hysterectomy/placental resolution Results: There were 81, 480 deliveries conducted during the study period of which 74 were identified as PAS. Hence PAS was seen in 1:1101 deliveries (0.09%). The estimated blood loss and number of units of blood products required were significantly higher in Group 1 (2.36 ± 0.77 l vs 1.8 ± 0.91 L, p = 0.002; and 10.17 ± 5.12 vs 6.77 ± 4.22, p = 0.005) compared to Group 2. The ICU stay was also more common in Group 1 (p = 0.01). The perinatal mortality was significantly higher in Group 1(45.71% vs 23.08%, p = 0.040). 79.7% women underwent primary cesarean hysterectomy while others were managed conservatively. In conservatively managed group, placental resolution took place in 60% and 40% required secondary hysterectomy. Conclusion: Antenatal diagnosis of placenta accreta spectrum disorders decreases the maternal morbidity and perinatal mortality.